Araucaria columnaris (Foster) Hooker - Sarrailh, Jean-Michel; Chauvin, Jean-Paul; Litaudon, Marc; Dumontet, Vincent; Pieters, Romuald (BOIS & FORETS DES TROPIQUES, 2004)
Le résumé est disponible dans le fichier PDF de l'article.